Ca-Sr isotope and chemical evidence for distinct sources of carbonatite and silicate mantle metasomatism. (1st November 2021) - Zhu, Hongli; Ionov, Dmitri A.; Du, Long; Zhang, Zhaofeng; Sun, Weidong
Abstract: Enrichments in light REE without concomitant enrichments in high-field-strength elements in mantle peridotites are usually attributed to inputs from carbonate-rich melts and referred to as 'carbonatite' metasomatism as opposed to interaction with evolved silicate melts. Alternatively, both enrichment types are ascribed to percolating volatile-bearing mafic liquids whose chemical signatures evolve from 'silicate' to 'carbonatite'. Here we compare these models for peridotites in which these enrichment types are combined, as may be common in the mantle. We report new Ca-Sr-Nd isotope and chemical data for lherzolite and harzburgite xenoliths from Spitsbergen that were metasomatized, first, by silicate, then by carbonate-rich melts that formed carbonate-bearing pockets replacing earlier minerals. Seven crushed samples were treated with acetic acid that dissolved carbonates formed in the latest event, but not silicates. The leachates (acid-removed carbonates making up 0.6–1.4% of total sample mass) contain much more Sr than the residues after leaching (277–2923 vs. 16–60 ppm), have a greater overall 87 Sr/ 86 Sr range (0.7049–0.7141 vs. 0.7036–0.7055) and higher 87 Sr/ 86 Sr in each sample than the residues. The leachates have lower δ 44/40 Ca range (0.17–0.68‰) than the residues (0.78–1.00‰), as well as lower δ 44/40 Ca than the residues in all samples but one. By and large, the carbonates are out of Ca-Sr isotope equilibrium with the host peridotites implying that the older silicate and younger carbonatite metasomatism were produced by different parental melts, thus supporting the existence of distinctive carbonate-rich metasomatic media in the lithospheric mantle, possibly including recycled materials. The δ 44/40 Ca in the leachates (i.e. carbonates, 0.17–0.68‰) are well below bulk silicate Earth (BSE) estimates (0.94 ± 0.05‰) and δ 44/40 Ca in non-metasomatized melt-depleted mantle. Yet, δ 44/40 Ca in the non-leached whole rock (WR) carbonate-bearing samples (0.75–0.95‰) fall within, or are only slightly lower than, the BSE range. The 87 Sr/ 86 Sr range in these WR samples (0.7030–0.7112) includes very high values for peridotites with large aggregates of dolomite and Mg-calcite. It appears that both carbonatite and silicate metasomatism may produce δ 44/40 Ca values lower than the BSE such that Ca-isotope data cannot robustly tell apart these two enrichment types, yet carbonatite metasomatism may yield the lowest δ 44/40 Ca. Carbonates, even at small mass fractions, are significant hosts of Sr in the WR Spitsbergen peridotites (8–51 wt.% of Sr mass) because of very high Sr concentrations, but add little to WR Ca balance (3–12 wt.%). As a result, high Sr content and 87 Sr/ 86 Sr ratios may be indices (though not definitive proofs) of carbonatite metasomatism in mantle rocks.